C-MYC empowers transcription and productive splicing of the oncogenic splicing factor Sam68 in cancer. Issue 12 (8th May 2019) - Caggiano, Cinzia; Pieraccioli, Marco; Panzeri, Valentina; Sette, Claudio; Bielli, Pamela
Abstract: The splicing factor Sam68 is upregulated in many human cancers, including prostate cancer (PCa) where it promotes cell proliferation and survival. Nevertheless, in spite of its frequent upregulation in cancer, the mechanism(s) underlying its expression are largely unknown. Herein, bioinformatics analyses identified the promoter region of the Sam68 gene ( KHDRBS1 ) and the proto-oncogenic transcription factor c-MYC as a key regulator of Sam68 expression. Upregulation of Sam68 and c-MYC correlate in PCa patients. c-MYC directly binds to and activates the Sam68 promoter. Furthermore, c-MYC affects productive splicing of the nascent Sam68 transcript by modulating the transcriptional elongation rate within the gene. Importantly, c-MYC-dependent expression of Sam68 is under the tight control of external cues, such as androgens and/or mitogens. These findings uncover an unexpected coordination of transcription and splicing of Sam68 by c-MYC, which may represent a key step in PCa tumorigenesis.